A Prophetic Guide for a Perplexed World: Louis Finkelstein and the 1940 Conference on Science, Philosophy, and Religion - Rock-Singer, Cara (Religion and American culture, 2019)
This article traces negotiations over the epistemic, ethical, and political authority of Judaism, Protestantism, Catholicism, and science in mid-twentieth-century America. Specifically, it examines how the president of the Jewish Theological Seminary, Rabbi Dr. Louis Finkelstein, led a diverse group of intellectual elites as they planned and convened the 1940 Conference on Science, Philosophy and Religion in Their Relation to the Democratic Way of Life (CSPR). Based on the conference's transcripts, proceedings, and papers, in addition to Finkelstein's writings from the period, this article shows how Finkelstein used his vision of the Jewish tradition as a model to form a pluralistic intellectual space that brought together the representatives of multiple religious traditions and modern science. To accredit the American way of life to Judaism, Finkelstein traced America's ethical values, democratic politics, and scientific genius back to the Hebrew Prophets through Rabbinic Judaism. In response to Finkelstein's historiography and the political and ideological challenges of World War II, scientific and religious experts negotiated their authority and debated how to mobilize their traditions in a quest for political stability. By analyzing the CSPR as a meeting of multiple discourses, this article reinstates science as a fundamental player in the story of American pluralism and demonstrates the way a non-Protestant tradition shaped the terms of an elite public's understanding of the "democratic way of life."